Pacesetter in Personalized Learning - Jacobs, Joanne (Education next, 2017)
The Chicago International Charter School (CICS) Irving Park's middle school is one of 130 schools nationwide piloting the Summit Learning Program (SLP), developed--and offered entirely free--by Summit Public Schools, a high-performing charter network based in California. Summit's eight schools, two of them in Washington State, are known for an approach that emphasizes both project-based and self-paced learning as well as the development of cognitive skills. In 2015, the network started sharing its model with schools throughout the country in an effort to improve their methods and spread their ideas. The tech mainstay of Summit's model is an online platform that the network developed with engineering help from Facebook. It comes loaded with a comprehensive, teacher-created curriculum, ideas for student projects, and assessments for grades 5 through 12 in core academic subjects. Students master academic content through personalized learning, choosing from "playlists" made of such learning tools as Khan Academy videos, BrainPOP animations, guided practice problems, interactive exercises, websites, and texts. They take tests when they feel ready, moving on to new content when they've achieved mastery. A blue line on the student's dashboard shows whether he or she is progressing at the expected pace. Technology is only part of Summit's model. Students spend most of their time learning cognitive skills and concepts through individual and collaborative "deeper learning" projects. Teachers work one-on-one with students, helping them set short-term and long-term goals and develop "habits of success," such as self-management, responsible decision making, and persistence. This article takes a look at the Summit Learning platform, how it began, and what the future holds for the Summit approach.